Clinical results of jugular-axillary approach for extracorporeal left ventricular assist device - Shilin Wang; Qianwen Liu; Ping Li; Changdong Zhang; Wenqian Wu; Hao Liu; Peiwen Yang; Lingyun Fang; Wei Su; Jamshid H. Karimov; Nianguo Dong; Shu Chen (Frontiers in Cardiovascular Medicine, 2026)
Objectives The traditional approach of placing the percutaneous extracorporeal left ventricular assist device (LVAD) through the femoral artery and vein has several downsides, primarily restricting patients’ movement and requiring a specific type of vein drainage cannula. To address this clinical limitation, we proposed a technique of placing the Extra-LVAD through the right axillary artery and jugular vein to bypass these issues. Methods Five patients underwent extra-LVAD implantation through the right axillary artery and jugular vein approach at Wuhan Union Hospital between May 2022 and January 2023. In this retrospective study, we compared echocardiographic parameters and dynamic lab data before and after LVAD support. Results All patients successfully bridged heart transplants with no major or minor adverse events, and no patient required an oxygenator during a median support duration of 10.0(±5.40) days. Hemodynamic support was effective, as evidenced by improved right ventricular function (tricuspid annular plane systolic excursion increased from 1.7 ± 0.2 to 1.9 ± 0.2; right ventricular area change rate from 33.2 ± 3.7% to 39.0 ± 8.0%) and stable end-organ perfusion markers (e.g., lactate and creatinine trends) maintained over 6 days post-implantation. Key physiological indicators, including mean arterial pressure, central venous pressure, renal and hepatic function markers remained stable or demonstrated improving trends over the 6-day post-implantation period. Post-transplant, 4 patients achieved a left ventricular ejection fraction above 60% without mechanical circulatory support, although one patient required an intra-aortic balloon pump. Conclusions In our 5-patient group, percutaneous insertion of an extra-LVAD through the right axillary artery and jugular vein may be viable and effective. This could be a favorable access point for future procedures. However, large samples and patient outcomes in different centers still need to be studied.